AN INVESTIGATION OF BOSE-EINSTEIN CORRELATIONS IN MUON-NUCLEON INTERACTIONS AT 490-GEV - Adams, M; Aid, S; Anthony, P; Baker, M; Bartlett, J; Bhatti, A; Botterweck, F; Braun, H; Busza, W; Conrad, J; Coutrakon, G; Davisson, R; et al. (1993)
An investigation of Bose-Einstein correlations amongst like-charged pions produced in muon-nucleon interactions at 490 GeV is presented. On top of a broader enhancement, a steep increase in the correlations at small four-momentum differences between the two pions is observed which may be explained by the contribution from decays of resonances (ρ{variant}-mesons). A two-dimensional analysis discriminates between two different parametrizations of the Bose-Einstein effect, strongly favoring the Lorentz-invariant parametrization over a parametrization based on a Gaussian source distribution in space and time. © 1993.